Preemptive kidney transplantation – the best method of renal replacement therapy - Rutkowski, Bolesław (Przewodnik Lekarza/Guide for GPs, 2012)
Preemptive kidney transplantation is becoming more and more popular in transplant community during last 10-15 years. This fact is quite important taking into account that in many studies better results of this mode of therapy was observed in comparison of the classic transplantation in patients after different period of dialysis therapy. Presented mode of treatment has to be preferred in children, adult person, elderly people and also in diabetic patients. This kind of therapy in Poland is promoted by nephrological-transplantological group from Gdansk. Successful preemptive transplant is strictly dependent from the existence of efficient program early identifying patients with chronic kidney disease.